Basalt fiber concrete and application thereof in truck scale

By surface modification of basalt fibers, the problem of poor interfacial performance in concrete is solved, the mechanical properties and durability of concrete are improved, and it is suitable for material preparation of automobile scales and extends the service life of the equipment.

CN119797869AActive Publication Date: 2025-04-11GUANGZHOU SINOSACLE WEIGHING EQUIP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411980929.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Due to the high chemical inertia and strong toughness in concrete, existing basalt fibers have poor interfacial performance with concrete substrates and reduced split tensile strength, which affects their application in automobile scales.

Method used

Silicone modified basalt fiber composition was prepared by reacting tetraethyl orthosilicate, p-toluenesulfonic acid, anhydrous ethanol and 3-glycidyl etheroxypropyl trimethoxysilane in a nitrogen atmosphere, and a silane coupling agent containing phosphate was obtained by click chemical synthesis, and the basalt fibers were further modified by 3-aminopropyl triethoxysilane to obtain modified fibers.

Benefits of technology

The bonding strength between basalt fiber and cement gel material is improved, the concrete's resistance to crack, seepage, shear and fatigue resistance is enhanced, the structural cross-sectional size and self-weight are reduced, and the service life of the car scale is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221534500000101
    Figure BDA0005221534500000101
  • Figure BDA0005221534500000111
    Figure BDA0005221534500000111
  • Figure BDA0005221534500000112
    Figure BDA0005221534500000112
Patent Text Reader

Abstract

The invention discloses basalt fiber concrete and application thereof in a truck scale, and relates to the technical field of reinforced concrete truck scales. The invention discloses basalt fiber concrete which comprises the following components in percentage by weight: 18-22% of a gel material, 25-30% of fine aggregate, 44-46% of coarse aggregate, 0.2-0.4% of a water reducing agent, 0.4-0.6% of modified fiber and 5-8% of water, and the sum of the weight percentages of the components is 100%. The preparation method comprises the following steps: organically modifying basalt fibers to obtain modified fibers; the modified fiber prepared by the invention is added into a concrete component, the modified fiber and a concrete base material have good interface bonding performance, and the prepared basalt fiber concrete has the characteristics of high mechanical strength and good toughness; and the service life of the truck scale is effectively prolonged when the reinforced concrete truck scale is applied to the reinforced concrete truck scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reinforced concrete truck scales, and in particular to basalt fiber concrete and application thereof in truck scales. Background Art

[0002] A truck scale, commonly known as a truck weighbridge, is a large-scale weighing device for checking the weight of motor vehicles on the ground. Truck scales have gone through two development stages: mechanical truck scales and electronic truck scales. At present, mechanical truck scales have been replaced by electronic truck scales that are easy to maintain and have accurate measurement. Electronic truck scales are still developing. Their sensors have developed from analog signal sensors to digital sensors, and weighing platforms have developed from all-steel structure platforms to steel frame cement structures, reinforced cement structures, and stainless steel concrete cement structures. Compared with all-steel structure electronic truck scales, cement structure electronic truck scales have the following advantages: (1) The strength of reinforced concrete is high; (2) Cement concrete is a non-metallic material with good corrosion and oxidation resistance. It does not need to be painted, which not only saves the painting process and reduces production costs, but also saves regular anti-rust maintenance; (3) The concrete platform is a non-good conductor, which can effectively prevent lightning strikes and avoid sensor damage; (4) Concrete is poured on site, which reduces the transportation cost of equipment. Although, the electronic truck scale with an all-steel structure carrier is currently widely used. However, the all-steel structure electronic truck scale platform is gradually being replaced by the cement structure electronic truck scale platform.

[0003] Active powder concrete is a high-performance concrete with high strength, good durability and good stability developed in the 1990s. The density of the matrix is ​​improved by optimizing the mixed particle grading, and the mechanical strength of the material is improved by adding silicon-containing materials such as fly ash as active ingredients. However, the brittleness of the concrete material increases accordingly. In order to solve this problem, fibers are usually added to the concrete material to enhance toughness. Basalt fiber is an environmentally friendly material made from natural basalt ore. It has excellent mechanical properties, corrosion resistance, high temperature resistance and electrical insulation properties and is widely used in the reinforcement of concrete materials. However, due to the strong toughness of basalt fiber, it cannot be made into a hook shape to enhance the mechanical anchoring effect, and the surface of basalt fiber is chemically inert, resulting in weak adhesion between the fiber and the cement matrix. As a result, although the addition of basalt fiber can effectively increase the ultimate tensile strength of concrete, the splitting tensile strength of concrete is reduced, affecting its application in truck scales. Although there is a solution in the prior art to graft nano-silica onto the surface of early basalt fiber and cooperate with silane coupling agent to improve the bonding strength between nano-silica, fiber and resin, nanoparticles have high specific surface area and surface activity. Nanoparticles are easy to aggregate due to their own characteristics, which directly affects the modification effect of nanoparticles. Summary of the invention

[0004] The purpose of the present invention is to provide a basalt fiber concrete and its application in a truck scale to solve the following technical problems:

[0005] The existing basalt fibers have poor interface performance with the concrete matrix due to their high surface chemical inertness and strong toughness. With the addition of basalt fibers, the splitting tensile strength of concrete decreases, affecting their application in truck scales.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A basalt fiber concrete comprises the following components in weight percentage: 18-22% gel material, 25-30% fine aggregate, 44-46% coarse aggregate, 0.2-0.4% water reducer, 0.4-0.6% modified fiber, 5-8% water, and the sum of the weight percentages of the components is 100%;

[0008] The preparation method of the modified fiber comprises the following steps:

[0009] A1: In a nitrogen atmosphere, tetraethyl orthosilicate, p-toluenesulfonic acid and anhydrous ethanol are added to a reaction kettle A and dispersed evenly, 3-glycidyloxypropyltrimethoxysilane is added, and the mixture is aged for 1-3 hours under stirring at room temperature, basalt fiber is added to the reaction kettle, and the mixture is reacted for 1-2 hours under stirring at room temperature, and the solvent is removed under reduced pressure to obtain an organosilicon-modified basalt fiber composition;

[0010] A2: 10-(2-methacryloyloxy) monodecyl phosphate, 3-mercaptopropyltriethoxysilane and benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation for 12-24 hours to obtain a modifier;

[0011] A3: Add the organosilicon-modified basalt fiber composition and 3-aminopropyltriethoxysilane into the reactor and disperse them evenly, control the temperature at 30-40°C, keep the reaction warm for 6-12 hours, adjust the pH to 6-7, continue to keep the reaction warm for 0.5-1 hour, add deionized water, dibutyltin dilaurate and modifier and disperse them evenly, keep the reaction warm for 6-9 hours, filter, wash and dry to obtain modified fiber.

[0012] Preferably, the addition ratio of tetraethyl orthosilicate, p-toluenesulfonic acid, anhydrous ethanol, 3-glycidyloxypropyltrimethoxysilane and basalt fiber in A1 is 5-8 mL: 0.04-0.06 g: 20-50 mL: 1-1.2 g: 10 g.

[0013] Preferably, the addition ratio of 10-(2-methacryloyloxy) monodecyl phosphate, 3-mercaptopropyltriethoxysilane and benzoin dimethyl ether in A2 is 0.9-1g: 1g: 0.1-0.2g.

[0014] Preferably, the addition ratio of the organosilicon-modified basalt fiber composition, 3-aminopropyltriethoxysilane, deionized water, dibutyltin dilaurate, and modifier in A3 is 10g: 4-6g: 0.6-1.2g: 10-20uL: 3-6g.

[0015] Preferably, the basalt fiber is a basalt chopped fiber with a length of 6-18 mm, a diameter of 10-15 um, an elastic modulus of 95-120 GPa, a compressive strength of 3200-4500 MPa, and an elongation at break of 2.5-25%.

[0016] Preferably, the gel material is obtained by mixing cement, fly ash and mineral powder in a mass ratio of 10:1.2-1.6:0.9-1.6.

[0017] Preferably, fine crushed stone and coarse crushed stone are mixed in a coarse aggregate mass ratio of 1:2-3; the particle size of the fine crushed stone is 5-10 mm; the particle size of the coarse crushed stone is 10-20 mm.

[0018] Preferably, the fine aggregate is river sand of Grade II grading with a fineness modulus of 2-3.

[0019] Preferably, the water reducer is a polycarboxylate water reducer.

[0020] Any of the above basalt fiber concrete is used in truck scales.

[0021] Beneficial effects of the present invention:

[0022] (1) The present application uses silane coupling agent and tetraethyl orthosilicate as precursors and solid acid-p-toluenesulfonic acid as a catalyst to modify the surface of basalt fiber to obtain an organosilicon-modified basalt fiber composition, which effectively improves the roughness and surface activity of the basalt fiber surface and enables the basalt fiber to have a stronger bonding effect with the cement gel material; the present application then uses the mercapto group of 3-mercaptopropyltriethoxysilane and the vinyl group of 10-(2-methacryloyloxy)monodecyl phosphate to undergo click chemistry synthesis to obtain a phosphate-containing silane coupling agent, i.e., a modifier; the present application then uses 3-aminopropyltriethoxysilane to modify the organosilicon-modified basalt fiber composition to obtain a basalt fiber having a large number of alkoxy groups on the surface; finally, the modifier is used to crosslink the basalt fiber having a large number of alkoxy groups on the surface prepared above to obtain a modified fiber.

[0023] The modified fiber prepared in this application is added to the concrete matrix to prepare basalt fiber concrete, which is a concrete material with high durability, high mechanical strength and good toughness; it has the characteristics of strong crack resistance, good impermeability, high rigidity, high strength, good shear resistance and fatigue resistance, and is used to make truck scales to effectively reduce the cross-sectional size of the structure, reduce the deadweight of the structure, prevent the truck scale from cracking and reduce deflection, greatly delay the time of crack appearance, and increase the durability of the component; improve the shear resistance of the material, the vertical component of the combined force of concrete and steel bars will offset part of the shear force, the shear resistance is improved, and the bearing capacity of the component is enhanced. The basalt fiber concrete material prepared in this application is used to prepare reinforced concrete truck scales, which is not only highly resistant to bending and compression, but also effectively reduces the occurrence of steel bar corrosion, greatly improving the service life of the truck scale.

[0024] (2) The modified fiber prepared in the present application is a basalt fiber with organic silicon molecular chains, phosphate groups and siloxane groups grafted onto its surface. The chemical reaction between the siloxane groups and the basalt fibers facilitates the organic molecular chains on the surface of the basalt fibers to coat the steel bars, forming a coupling agent layer on the surface of the steel bars, thereby improving the interface bonding between the concrete and the steel bar matrix. The phosphate groups on the surface of the modified fiber can form a dense phosphate protective film with the steel bar metal, passivating the metal surface, preventing water molecules and other salt ions from contacting the metal, and achieving the effect of preventing steel bar corrosion.

[0025] (3) The present application uses a composite of cement, fly ash and mineral powder as a gel material to prepare a multi-component gel material system. The different finenesses of cement, fly ash and mineral powder are compounded to significantly improve the particle grading of the material, increase the density of concrete, and improve the mechanical strength of concrete. Moreover, the hydration reaction of fly ash and mineral powder under alkaline conditions produces a super-superposition phenomenon, which improves the elastic modulus of concrete through synergistic effect. DETAILED DESCRIPTION

[0026] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1 The preparation method of modified fiber comprises the following steps:

[0028] A1: In a nitrogen atmosphere, 5 mL of tetraethyl orthosilicate, 0.04 g of p-toluenesulfonic acid, and 20 mL of anhydrous ethanol were added to a reactor A and dispersed evenly, 1 g of 3-glycidyloxypropyltrimethoxysilane was added, and the mixture was aged for 1 h under stirring at room temperature. 10 g of basalt fiber (diameter 13 um, length 12 mm, elastic modulus 99.21 GPa, compressive strength 3788.1 MPa, elongation at break 4.0%) was added to the reactor, and the mixture was reacted for 1 h under stirring at room temperature. The solvent was removed under reduced pressure to obtain a silicone-modified basalt fiber composition.

[0029] A2: 9 g of 10-(2-methacryloyloxy) monodecyl phosphate, 10 g of 3-mercaptopropyltriethoxysilane, and 1 g of benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation conditions for 12 h (20 W ultraviolet lamp, 365 nm wavelength light) to obtain a modifier;

[0030] A3: Add 10g of organosilicon-modified basalt fiber composition and 4g of 3-aminopropyltriethoxysilane into the reactor and disperse them evenly. Control the temperature at 30°C and keep the reaction for 6h. Add glacial acetic acid to adjust the pH to 6 and keep the reaction for 0.5h. Add 0.6g of deionized water, 10uL of dibutyltin dilaurate and 3g of modifier and disperse them evenly. Keep the reaction for 6h. Filter, wash and dry to obtain modified fiber.

[0031] Embodiment 2 The preparation method of modified fiber comprises the following steps:

[0032] A1: In a nitrogen atmosphere, 6.5 mL of tetraethyl orthosilicate, 0.05 g of p-toluenesulfonic acid, and 35 mL of anhydrous ethanol were added to a reactor A and dispersed evenly, 1.1 g of 3-glycidyloxypropyltrimethoxysilane was added, and the mixture was aged for 1-3 h under stirring at room temperature. 10 g of basalt fiber (diameter 13 um, length 12 mm, elastic modulus 99.21 GPa, compressive strength 3788.1 MPa, elongation at break 4.0%) was added to the reactor, and the mixture was reacted for 1.5 h under stirring at room temperature. The solvent was removed under reduced pressure to obtain a silicone-modified basalt fiber composition;

[0033] A2: 9.5 g of 10-(2-methacryloyloxy) monodecyl phosphate, 10 g of 3-mercaptopropyltriethoxysilane, and 1.5 g of benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation conditions for 18 h (20 W ultraviolet lamp, 365 nm wavelength light) to obtain a modifier;

[0034] A3: Add 10g of organosilicon-modified basalt fiber composition and 5g of 3-aminopropyltriethoxysilane into the reactor and disperse them evenly. Control the temperature at 35°C and keep the reaction for 9h. Add glacial acetic acid to adjust the pH to 6 and keep the reaction for 0.5h. Add 1g of deionized water, 15uL of dibutyltin dilaurate and 4.5g of modifier and disperse them evenly. Keep the reaction for 6h. Filter, wash and dry to obtain modified fiber.

[0035] Embodiment 3 The preparation method of modified fiber comprises the following steps:

[0036] A1: In a nitrogen atmosphere, 8 mL of tetraethyl orthosilicate, 0.06 g of p-toluenesulfonic acid, and 50 mL of anhydrous ethanol were added to a reactor A and dispersed evenly, 1.2 g of 3-glycidyloxypropyltrimethoxysilane was added, and the mixture was aged for 3 h under stirring at room temperature. 10 g of basalt fiber ((diameter 13 um, length 12 mm, elastic modulus 99.21 GPa, compressive strength 3788.1 MPa, elongation at break 4.0%)) was added to the reactor, and the mixture was reacted for 1-2 h under stirring at room temperature, and the solvent was removed under reduced pressure to obtain a silicone-modified basalt fiber composition;

[0037] A2: 10 g of 10-(2-methacryloyloxy) monodecyl phosphate, 10 g of 3-mercaptopropyltriethoxysilane, and 2 g of benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation conditions for 24 h (20 W ultraviolet lamp, 365 nm wavelength light) to obtain a modifier;

[0038] A3: Add 10g of organosilicon-modified basalt fiber composition and 6g of 3-aminopropyltriethoxysilane into the reactor and disperse them evenly. Control the temperature at 40°C and keep the reaction for 12h. Add glacial acetic acid to adjust the pH to 7 and keep the reaction for 1h. Add 1.2g of deionized water, 20uL of dibutyltin dilaurate and 6g of modifier and disperse them evenly. Keep the reaction for 9h. Filter, wash and dry to obtain modified fiber.

[0039] Example 4 The preparation method of basalt fiber concrete comprises the following steps:

[0040] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of the modified fiber prepared in Example 1 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0041] Example 5 The preparation method of basalt fiber concrete comprises the following steps:

[0042] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of the modified fiber prepared in Example 2 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0043] Example 6 The preparation method of basalt fiber concrete comprises the following steps:

[0044] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of the modified fiber prepared in Example 3 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0045] Comparative Example 1 The preparation method of the modified fiber comprises the following steps:

[0046] In a nitrogen atmosphere, 6.5 mL of tetraethyl orthosilicate, 0.05 g of p-toluenesulfonic acid, and 35 mL of anhydrous ethanol were added to reactor A and dispersed evenly, 1.1 g of 3-glycidyloxypropyltrimethoxysilane was added, and aged for 1-3 h under stirring at room temperature. 10 g of basalt fiber (diameter 13 um, length 12 mm, elastic modulus 99.21 GPa, compressive strength 3788.1 MPa, elongation at break 4.0%) was added to the reactor, reacted for 1.5 h under stirring at room temperature, and the solvent was removed under reduced pressure to obtain a silicone-modified basalt fiber composition.

[0047] Comparative Example 2 The preparation method of the modified fiber comprises the following steps:

[0048] A1: 9.5 g of 10-(2-methacryloyloxy) monodecyl phosphate, 10 g of 3-mercaptopropyltriethoxysilane, and 1.5 g of benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation conditions for 18 h (20 W ultraviolet lamp, 365 nm wavelength light) to obtain a modifier;

[0049] A2: 10g basalt fiber (diameter 13um, length 12mm, elastic modulus 99.21GPa, compressive strength 3788.1MPa, elongation at break 4.0%) and 5g 3-aminopropyltriethoxysilane were added into the reactor and dispersed evenly. The temperature was controlled at 35°C and kept warm for 9h. Glacial acetic acid was added to adjust the pH to 6 and kept warm for 0.5h. 1g deionized water, 15uL dibutyltin dilaurate and 4.5g modifier were added and dispersed evenly. The reaction was kept warm for 6h. The modified fiber was filtered, washed and dried to obtain the modified fiber.

[0050] Comparative Example 3 The preparation method of the modified fiber comprises the following steps:

[0051] A1: In a nitrogen atmosphere, 6.5 mL of tetraethyl orthosilicate, 0.05 g of p-toluenesulfonic acid, and 35 mL of anhydrous ethanol were added to a reactor A and dispersed evenly, 1.1 g of 3-glycidyloxypropyltrimethoxysilane was added, and the mixture was aged for 1-3 h under stirring at room temperature. 10 g of basalt fiber (diameter 13 um, length 12 mm, elastic modulus 99.21 GPa, compressive strength 3788.1 MPa, elongation at break 4.0%) was added to the reactor, and the mixture was reacted for 1.5 h under stirring at room temperature. The solvent was removed under reduced pressure to obtain a silicone-modified basalt fiber composition;

[0052] A2: 10g of organosilicon-modified basalt fiber composition and 5g of 3-aminopropyltriethoxysilane were added to the reactor and dispersed evenly. The temperature was controlled at 35°C and the reaction was kept warm for 9h. Glacial acetic acid was added to adjust the pH to 6 and the reaction was continued for 0.5h. 1g of deionized water and 15uL of dibutyltin dilaurate were added and the reaction was kept warm for 6h. The mixture was filtered, washed and dried, and then mixed evenly with 2.2g of 10-(2-methacryloyloxy) monodecyl phosphate to obtain modified fiber.

[0053] Comparative Example 4 The preparation method of basalt fiber concrete comprises the following steps:

[0054] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of the modified fiber prepared in Comparative Example 1 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0055] Comparative Example 5 The preparation method of basalt fiber concrete comprises the following steps:

[0056] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of modified fiber prepared in Comparative Example 2 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0057] Comparative Example 6 The preparation method of basalt fiber concrete comprises the following steps:

[0058] 158g P.0 42.5 silicate cement, 19g fly ash (F class I fly ash), 17g mineral powder (S95 grade slag), 270g fine aggregate (II graded river sand, fineness modulus 2.5), 135g fine crushed stone (particle size of 5-10mm), 307g coarse crushed stone (particle size of 10-20mm), 2g polycarboxylic acid water reducer (BASF melflix-1641f high-efficiency polycarboxylic acid solid water reducer produced by BASF-Degussa, Germany) are blended, 40mL of water is added for blending, 5g of the modified fiber prepared in Comparative Example 3 is added for blending, and 47mL of water is added for blending to obtain basalt fiber concrete.

[0059] Performance Testing

[0060] The basalt fiber concrete prepared in Example 4-6 and Comparative Example 4-6 was cured for 7 days and 28 days at a temperature of 20°C and a RH of 95%, and the following tests were performed;

[0061] (1) Mechanical properties: The test was carried out in accordance with GB / T 50081-2002 “Test methods for mechanical properties of ordinary concrete”, and the mechanical properties of compressive strength and splitting tensile strength were tested using a TSY-2000 pressure testing machine;

[0062] ①Compressive strength: specimen size 150×150×150m 3 , and calculate the compressive strength Fcu according to the following formula:

[0063] Fcu=F / A

[0064] Where, Fcu-compressive strength, MPa; F-specimen failure load, N; A-specimen pressure bearing area, mm 2 ; The calculation results are shown in Table 1;

[0065] ② Splitting tensile strength: specimen size 150×150×150m 3 , place the specimen on a steel positioning bracket, use a steel pad, and then perform the splitting tensile strength test under a pressure testing machine. Set the loading speed to 0.06kN / S. During the test, the loading speed is uniform and continuous, and the splitting tensile strength Fts is calculated according to the following formula:

[0066] Fts=2F / (Aπ)

[0067] Where, Fts-splitting tensile strength, MPa; F-specimen failure load, N; A-specimen pressure area, mm 2 ; The calculation results are shown in Table 1;

[0068] ③ Flexural strength: specimen size 550×150×150m 3 , set the load speed to 0.06kN / S, the loading speed is uniform and continuous during the test, and the flexural strength Fb is calculated according to the following formula:

[0069] Fb=Fl / (bh 2 )

[0070] Where, Fb-flexural strength, MPa; F-specimen failure load, N; l-spacing of supports under the specimen during loading test, mm; b-width of the specimen section, mm; h-height of the specimen section, mm; the calculation results are shown in Table 1.

[0071] Table 1: Statistical table of mechanical properties test data of Examples 4-6 and Comparative Examples 4-6

[0072]

[0073]

[0074] It can be seen from Table 1 that the modified fiber prepared in the present application is added to concrete, which effectively strengthens the ability of concrete materials to resist cracks of various levels and achieves the reinforcement and toughening of concrete.

[0075] (2) Slump: The test was conducted according to GB / T 50080-2016 “Standard for Test Methods for Properties of Ordinary Concrete Mixtures”. The test results are shown in Table 2.

[0076] (3) Electric flux: The test was conducted according to GB / T 50081-2009 “Test methods for long-term performance and durability of ordinary concrete”. The strength-size conversion factor was 0.8 for fiber concrete. The test results are shown in Table 2.

[0077] (4) Anti-corrosion performance: According to the "Test Method for Port Engineering Concrete", the steel bars were placed in the basalt fiber concrete prepared in Example 4-6 and Comparative Example 4-6 for curing and forming. The curing environment was 20°C and RH95% for 8 days. After being immersed in water for 24 hours, the steel bars were taken out and dried (30°C and dried for 2 days). The above immersion and drying steps were repeated five times. The test pieces were split and the weight loss rate and rust accumulation rate of the steel bars were measured after treatment. The test results are shown in Table 2.

[0078] Table 2: Statistical table of performance test data of Examples 4-6 and Comparative Examples 4-6

[0079]

[0080]

[0081] As can be seen from Table 2, the modified fiber prepared in the present application is added to concrete, which effectively improves the density of the concrete and thus improves the durability of the concrete; the present application organically modifies the basalt fiber, and the organic molecular chains on the surface of the modified fiber coat the surface of the steel bar, thereby giving the steel bar arranged in the concrete corrosion resistance, thereby greatly improving the service life of the truck scale prepared using the basalt fiber concrete of the present application.

[0082] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A basalt fiber concrete, characterized in that: The invention comprises the following components in weight percentage: 18-22% gel material, 25-30% fine aggregate, 44-46% coarse aggregate, 0.2-0.4% water reducing agent, 0.4-0.6% modified fiber, 5-8% water, and the sum of the weight percentages of the components is 100%; The preparation method of the modified fiber comprises the following steps: A1: In a nitrogen atmosphere, tetraethyl orthosilicate, p-toluenesulfonic acid and anhydrous ethanol are added to a reaction kettle A and dispersed evenly, 3-glycidyloxypropyltrimethoxysilane is added, and the mixture is aged for 1-3 hours under stirring at room temperature, basalt fiber is added to the reaction kettle, and the mixture is reacted for 1-2 hours under stirring at room temperature, and the solvent is removed under reduced pressure to obtain an organosilicon-modified basalt fiber composition; A2: 10-(2-methacryloyloxy) monodecyl phosphate, 3-mercaptopropyltriethoxysilane and benzoin dimethyl ether were added to a glass reaction bottle and dispersed evenly, and treated under ultraviolet irradiation for 12-24 hours to obtain a modifier; A3: Add the organosilicon-modified basalt fiber composition and 3-aminopropyltriethoxysilane into the reactor and disperse them evenly, control the temperature at 30-40°C, keep the reaction warm for 6-12 hours, adjust the pH to 6-7, continue to keep the reaction warm for 0.5-1 hour, add deionized water, dibutyltin dilaurate and modifier and disperse them evenly, keep the reaction warm for 6-9 hours, filter, wash and dry to obtain modified fiber.

2. The basalt fiber concrete according to claim 1, characterized in that: The addition ratio of tetraethyl orthosilicate, p-toluenesulfonic acid, anhydrous ethanol, 3-glycidyloxypropyltrimethoxysilane, and basalt fiber in A1 is 5-8 mL: 0.04-0.06 g: 20-50 mL: 1-1.2 g: 10 g.

3. The basalt fiber concrete according to claim 1, characterized in that: The addition ratio of 10-(2-methacryloyloxy) monodecyl phosphate, 3-mercaptopropyltriethoxysilane, and benzoin dimethyl ether in A2 is 0.9-1g: 1g: 0.1-0.2g.

4. The basalt fiber concrete according to claim 1, characterized in that: The addition ratio of the organosilicon-modified basalt fiber composition, 3-aminopropyltriethoxysilane, deionized water, dibutyltin dilaurate, and modifier in A3 is 10g: 4-6g: 0.6-1.2g: 10-20uL: 3-6g.

5. The basalt fiber concrete according to claim 1, characterized in that: The basalt fiber is a basalt short-cut fiber with a length of 6-18 mm, a diameter of 10-15 um, an elastic modulus of 95-120 GPa, a compressive strength of 3200-4500 MPa, and an elongation at break of 2.5-25%.

6. The basalt fiber concrete according to claim 1, characterized in that: The gel material is obtained by mixing cement, fly ash and mineral powder in a mass ratio of 10:1.2-1.6:0.9-1.

6.

7. The basalt fiber concrete according to claim 1, characterized in that: The coarse aggregate is obtained by mixing fine crushed stone and coarse crushed stone in a mass ratio of 1:2-3; the particle size of the fine crushed stone is 5-10mm; the particle size of the coarse crushed stone is 10-20mm.

8. The basalt fiber concrete according to claim 1, characterized in that: The fine aggregate is river sand of grade II grading, with a fineness modulus of 2-3.

9. The basalt fiber concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

10. The basalt fiber concrete according to any one of claims 1 to 9 is used in a truck scale.

Citation Information

Patent Citations

  • Basalt fiber reinforced cement based material and preparation method therefor

    CN105541209A

  • SiO2 nanoparticle modified thermosetting impregnating agent for basalt fiber composite ribs, and preparation method thereof

    CN111138093A

  • Corrosion-resistant concrete with good permeability resistance and preparation method thereof

    CN118529978A

  • Repair and Seismic Retrofitting method of Concrete Structures by using Fiber Reinforced Plastic 〔FRP〕 Rebar

    KR101560804B1

  • Anti-explosion and Anti-impact multi-stage heterogeneous fiber preform composite concrete and preparation method therefor

    WO2021077667A1